ON THE ISSUE OF DIACHRONIC TYPOLOGICAL RESEARCH - Ergasheva Asel Erkinovna (Western European Studies, 2024)
The article deals with the problem of the correlation of synchronous and diachronic approaches to language analysis. Modern advances in semantics and linguocognitivistics, based on the influence of cognitive factors on the semantic development of words, raise the question of how to combine these approaches. In this paper, it is proposed to overcome one– sidedness in the university training of linguists in order to more fully take into account both aspects – synchrony and diachrony - in the analysis of language
Keywords: Theoretical linguistics; semantics; synchronic research